2019
DOI: 10.1002/pat.4546
|View full text |Cite
|
Sign up to set email alerts
|

Application of a bio‐based polyester plasticizer modified by hydrosilicon‐hydrogenation reaction in soft PVC films

Abstract: A kind of bio‐based plasticizer, poly (hexanediol maleic) (MH), was synthesized using 1,6‐hexalene and maleic acid as raw materials, and it was modified by hydrosilicon‐hydrogenation reaction to improve its plasticizing efficiency. The chemical structure and plasticizing performance of MH and its modification product (MHA) were characterized by Fourier‐transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance (1H‐NMR), X‐ray photoelectron spectroscopy (XPS), and Dynamic mechanical analysis (DMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Siloxanes exhibit also good thermal stability, hydrophobicity, and nontoxicity. Consequently, Ji et al [ 22 ] reported the use of poly(maleic acid hexanediol) ester (MH) modified with 10% (MHA-1) and 20% (MHA-2) of the maleic anhydride amount with 1,1,3,3-tetramethyldisiloxane (TMDS). The hydrosilylation reaction was carried out with the use of an unsaturated bond of maleic acid.…”
Section: New Primary Plasticizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Siloxanes exhibit also good thermal stability, hydrophobicity, and nontoxicity. Consequently, Ji et al [ 22 ] reported the use of poly(maleic acid hexanediol) ester (MH) modified with 10% (MHA-1) and 20% (MHA-2) of the maleic anhydride amount with 1,1,3,3-tetramethyldisiloxane (TMDS). The hydrosilylation reaction was carried out with the use of an unsaturated bond of maleic acid.…”
Section: New Primary Plasticizersmentioning
confidence: 99%
“…The most common types of intermolecular forces of attraction present in PVC–plasticizer blends are van der Waals forces, including dipole–dipole and dipole-induced dipole attractions, London dispersion forces, as well as hydrogen bonds. The dipole–dipole interactions occur between the polar groups of plasticizers, like carbonyl in ester linkages [ 21 ] or oxygen in Si-O-Si linkages [ 22 ] and chlorine atoms in PVC backbone. In a plasticizer molecule, a hydrogen bonding may appear between the carbonyl groups of the ester and the hydrogen attached to the carbon in an α position relative to the carbon–chlorine bonds in PVC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Among these plasticizers, phthalates occupy more than 75% of the consumption of all the plasticizers. 6,7 Nevertheless, the plasticizers of phthalate are carcinogenic and easily migrate out of the PVC. Furthermore, the migrated plasticizers will cause reproductive toxicity, 8 threaten human health and pollute the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more than 6.4 million tons of plasticizers are produced worldwide per year, and most of them are used in PVC 4,5 . Among these plasticizers, phthalates occupy more than 75% of the consumption of all the plasticizers 6,7 . Nevertheless, the plasticizers of phthalate are carcinogenic and easily migrate out of the PVC.…”
Section: Introductionmentioning
confidence: 99%